Sperm subpopulations in ejaculated sperm and spermatozoa recovered from ovine epididymides up to 48 h after death - Bergstein-Galan, Tácia Gomes; Weiss, Romildo Romualdo; Kozicki, Luiz Ernandes; Bicudo, Sony Dimas [UNESP] (Elsevier, 2017)
The objectives of this study were threefold: to identify subpopulations of sperm based on the kinetics of frozen/thawed sheep epididymal spermatozoa or semen collected with an artificial vagina; to evaluate the effects on sperm subpopulations in the thawed samples of post mortem storage at room temperature and the addition of 20% of seminal plasma to the freezing extender and to correlate the percentage of subpopulations with gestation rate following artificial intrauterine insemination. The categorization of the subpopulations was based on sperm kinetic data from Computer Assisted Sperm Analysis (CASA). A hundred ewes were inseminated with thawed spermatozoa and gestation rate was correlated with the proportions of each subpopulation using Pearson correlation matrix and linear regression. Three distinct subpopulations were identified in the thawed samples of either ovine ejaculate collected in artificial vaginas (AV) or ovine spermatozoa retrieved from the cauda epididymis. Subpopulation 1 (SP1) was characterized by spermatozoa with slow and non-linear motion, subpopulation 2 (SP2) was classified as hyperactived spermatozoa and subpopulation 3 (SP3) was composed of spermatozoa with fast, linear motion. The largest subpopulation in all groups was SP1. The semen collected in an artificial vagina had a higher (P < 0.05) percentage of SP2 and lower (P <0.05) percentage of SP1 when compared to spermatozoa recovered after death. Increasing time of storage after death had a detrimental effect on sperm samples, increasing (P < 0.05) the percentage of SP1 and decreasing (P < 0.05) SP2. Length of storage after death was the only variable that influenced, with an inversely proportional relationship, SP3. In samples stored for 48 h after death no SP3 spermatozoa were present. The addition of seminal plasma to the cryopreservative decreased (P < 0.05) the subpopulation of hyperactived spermatozoa (SP2). We conclude that, after thawing there are three sperm subpopulations in the spermatozoa obtained from the cauda epididymides and the semen collected in AVs and that the relative proportions of these subpopulations varies with the time of storage post mortem and the presence of 20% of seminal plasma in the extender. However, we conclude that these subpopulations do not correlate with fertility after intrauterine artificial insemination.
Keywords: Motion pattern; Ram; Seminal plasma